Characterization and mycotoxin analysis of Fusarium spp. from highland areas in Malaysia - Nurhazriati Manshor,; Nurul Farizah Azuddin,; Masratul Hawa Mohd,; Nik Mohd Izham Mohamed Nor,; Latiffah Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fusarium isolates from highland areas in Malaysia were mostly recovered from two species of grasses, Elyhordeum montanense and Paspalum conjugatum. The isolates were grouped into four morphological groups. Based on TEF-1α sequences, morphotype 1 isolates were molecularly identified as F. graminearum species complex, morphotype 2 as F. venenatum, morphotype 3 as F. avenaceum and morphotype 4 as F. kyushuense. Restriction analysis of the Intergenic Spacer region showed high levels of genetic diversity of isolates in F. graminearum species complex and F. venenatum. For mycotoxin analysis, only F. avenaceum and F. kyushuense produced beauvericin and moniliformin (0.869 & 0.321 µg/kg, respectively). Zearalenone was produced by 32 isolates of F. graminearum species complex (0.002 – 0.437 µg/kg), two isolates of F. venenatum (0.006 - 0.014 µg/kg) and F. kyushuense (0.006 µg/kg). Only F. avenaceum isolate produced fumonisin B1 (0.001 µg/kg). The present study indicates the occurrence of Fusarium species commonly reported in highland areas in Malaysia where the weather is cooler and the temperature is lower than in the lowland areas. To our knowledge, this is the first report on the occurrence of phylogenetic species within F. graminearum species complex, F. venenatum, F. avenaceum and F. kyushuense in Malaysia.